2021
DOI: 10.3390/nu13030809
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K and D Supplementation and Bone Health in Chronic Kidney Disease—Apart or Together?

Abstract: Vitamin K (VK) and vitamin D (VD) deficiency/insufficiency is a common feature of chronic kidney disease (CKD), leading to impaired bone quality and a higher risk of fractures. CKD patients, with disturbances in VK and VD metabolism, do not have sufficient levels of these vitamins for maintaining normal bone formation and mineralization. So far, there has been no consensus on what serum VK and VD levels can be considered sufficient in this particular population. Moreover, there are no clear guidelines how supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 230 publications
0
14
0
2
Order By: Relevance
“…Iron deficit is actively sought after and treated with specific replacement regimens [ 56 ]. Vitamin K supplementation is advised in bone and inflammatory rheumatic disease, chronic renal failure and for the prevention of vascular calcification and cardiovascular disease [ 57 , 58 , 59 , 60 ]; however, is it hardly mentioned in the nutritional guidelines for IBD patients. This attitude should change in order to reduce the adjunctive risk factor of osteoporosis in already high-risk patients, prevent coagulation defects and possibly help modulate inflammatory responses in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Iron deficit is actively sought after and treated with specific replacement regimens [ 56 ]. Vitamin K supplementation is advised in bone and inflammatory rheumatic disease, chronic renal failure and for the prevention of vascular calcification and cardiovascular disease [ 57 , 58 , 59 , 60 ]; however, is it hardly mentioned in the nutritional guidelines for IBD patients. This attitude should change in order to reduce the adjunctive risk factor of osteoporosis in already high-risk patients, prevent coagulation defects and possibly help modulate inflammatory responses in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ALP activity was increased significantly in human Caco-2 cells by MK-4 treatment, disclosing similar biochemical properties to the typical IALP [ 137 ]. Several observational and interventional studies have reported that CKD patients undergoing conservative or artificial renal replacement therapy (hemodialysis or PD) suffer from subclinical vitamin K deficiency, related to dietary regimen and overall poor nutrient intake [ 138 , 139 ]. The effect of vitamin K on bone strength mainly manifests through the vitamin K-dependent carboxylation and consequent activation of osteocalcin and MGP.…”
Section: Vitamin K and Balpmentioning
confidence: 99%
“…A meta-analysis of 15 RCTs [93] and several other RCTs showed that vitamin D supplementation combined with calcium resulted in a statistically significant decreased risk of fractures among older women [94][95][96][97][98][99]. Also, meta-analysis of 47 RCTs encompassing 58,424 patients demonstrated that vitamin D with calcium supplement showed benefits in fracture reduction [100] and was effective in preventing bone fractures in several chronic diseases [101][102][103][104]. According to a review of RCTs, including residential care and community-dwelling elders, only a few trials demonstrated fracture risk reduction with vitamin D treatment [106], and several RCTs of vitamin D alone do not show any benefits for fracture reduction [105,[107][108][109][110][111]113].…”
Section: Fracturementioning
confidence: 99%